The interactive effect of sandprawn (Callichirus kraussi) stebbing bioturbation and nutrients on macrofaunal communities - Cooper, Rachel (Department of Biological Sciences, 2014)
My thesis combined an observational study and field and laboratory experiments to investigate how nutrients and bioturbation by C. kraussi interact to structure macrofaunal communities and how ambient temperatures influence these factors.